Application of the C4.5 Algorithm Determination of Depreciation Classification Volume of Fertilizer on Storage Warehouse - Y Yendrizal (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2021)
The problems faced by the fertilizer warehouse PT. Iskandar Muda currently shrinking the volume of fertilizer for storage in warehouses, which is often reduced, is not yet known by the management. In reducing the volume of this fertilizer, the author wants to apply the C4.5 Algorithm to help in making decisions. From all the existing data will be classified and predicted, from the classification results will present the rules. So that it can be easily understood in natural language. Based on the application of the C4.5 Algorithm in the classification technique of fertilizer volume shrinkage on storage in the warehouse at the Pupuk Iskandar Muda warehouse, the results of this study show that 1) the C4.5 algorithm with the decision tree method can provide executive information and the system is used to describe processes related to depreciation classification. 2) The C4.5 algorithm is considered as an algorithm that is very helpful in classifying data because the characteristics of the classified data can be obtained clearly, both in the form of a decision tree structure and rules or rule-if-then. 3) Form a decision tree in providing recommendations for decision making.